Design Thinking Uncovered through Students’ Experiences and Participation: A Grounded Theory Study - Lorenzana-Mamauag, Ruby A. (International Journal of Psychosocial Rehabilitation, 2020)
Design Thinking as an extension modality has been introduced to the Isabela State University through the Learning Express Program in collaboration with Singapore Polytechnic and the Philippine Association for State Universities and Colleges. Filipino students have participated in this program as student buddies/counterparts of the students from Singapore to collaborate and apply design thinking to identify needs of the community and to offer their solutions to the unmet needs of the community. This qualitative study was conducted to better understand Design Thinking through the experiences and perceptions of the ISU students exposed in Design Thinking in their participation to the Learning Express Program as an extension modality and as an authentic teaching strategy. The study utilized the coding methods of the Grounded Theory in the analysis of the data from student participants. It was grounded on the study that the students perceived Design Thinking as an extension modality to be need-driven, human-centered, problem solving methodology that addresses the most pressing need of the community. Students engage in empathy, ideation and prototyping to help the community find solution to their needs. Students viewed it as stressful, challenging yet fulfilling teaching strategy that is authentic, collaborative and meaningful method to produce students who possessed the 21st century skills: critical thinker, creative, innovative, good communicator and empathic to the members of the society.